Monitoring of water processes using intelligent condition indicators. Issue 1 (2015) - Liukkonen, Mika; Hiltunen, Yrjö; Laakso, Ilkka; Juntunen, Petri
Abstract: Water quality is an increasingly important issue, because water is the mostly used raw material in the world and poor quality water causes many difficult issues in societies and ecosystems. Industrial wastewater treatment, for instance, is facing big challenges concerning fulfilment of both general and plant-specific regulations concerning their effluents and cost management of treatment plants. The wastewater coming from the pulp and paper industry contains substances such as nutrients (phosphorus, nitrogen) and solid organic material, which in large quantities are considered harmful to the ecosystem, so competent treatment is required and the treatment efficiency has to be monitored and controlled carefully and continuously. Nonetheless, it seems that the overall operation of the treatment plants needs to be improved, if the water industry is to satisfy regulations for increased efficiency (O'Brien et al., 2011).